2001
DOI: 10.1038/35102031
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the atomic arrangements on the high-temperature reconstructed α-Al2O3(0001) surface

Abstract: Alumina is a technologically important oxide crystal because of its use as a catalyst and as a substrate for microelectronic applications. A precise knowledge of its surface atomic structure is a prerequisite for understanding and controlling the physical processes involved in many of its applications. Here we use a dynamic scanning force microscopy technique to image directly the atomic structure of the high-temperature phase of the alpha-Al2O3(0001) surface. Evidence for a surface reconstruction appears as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
203
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(215 citation statements)
references
References 21 publications
8
203
0
Order By: Relevance
“…[3][4][5][6] Only recently, experimental and theoretical methods have established a relatively clear picture of this surface in ultra high vacuum. 5,[7][8][9][10] A full understanding of the environment dependent structure and reactivity of the ͑0001͒ ␣-Al 2 O 3 surface is hampered, however, by some discrepancies between the experimental observations 7-9 and theoretical predictions. 5,10 The discrepancies are believed to be related to the hydration of the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Only recently, experimental and theoretical methods have established a relatively clear picture of this surface in ultra high vacuum. 5,[7][8][9][10] A full understanding of the environment dependent structure and reactivity of the ͑0001͒ ␣-Al 2 O 3 surface is hampered, however, by some discrepancies between the experimental observations 7-9 and theoretical predictions. 5,10 The discrepancies are believed to be related to the hydration of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Eng et al, 4 have shown that the structure of the ͑0001͒ surface of dense ␣-phase alumina exposed to water vapor is part way between that of stoichiometric ␣-Al 2 O 3 and ␥-Al(OH) 3 ͑gibbsite, bayerite͒, i.e., different to that observed under UHV. [7][8][9] Hydroxylation is of special importance for alumina, as surfaces of all phases of alumina are almost always covered by water, either dissociated or molecular. 6,11 McHale et al 11,12 showed that the amount of surface hydroxyl groups varies from ϳ15 OH/nm 2 at a surface area of 150 m 2 /g and 600 K to ϳ3 OH/nm 2 at 30 m 2 /g and 1400 K for the porous ␣ phase.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, non-contact atomic force microscopy (nc-AFM) has improved dramatically and it is now possible to obtain atomic resolution images [1] of a large range of surfaces; semiconductors [2], metals [3], and pure insulators [4] in ultrahigh vacuum (UHV) conditions. Measurement of tip-sample forces and dissipation of energy as a function of separation [5][6][7] is also possible and will probably shed light into a number of interesting problems like atomic manipulation, atomic scale friction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The method should prove valuable in determining the chemical forces in atomic force microscopy (AFM). Thus far, a perturbation method to treat these forces, which are at the bottom of atomic resolution [24,25], has proved elusive. As shown here, these forces can be calculated from the overlap of the wave functions of the decoupled systems and a single point of the energy curve of the coupled system.…”
mentioning
confidence: 99%